2018
DOI: 10.14423/smj.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Adults and Children: A 10-Year Case Series at Two Large Academic Hospitals in Houston, Texas

Abstract: The designations employed and the presentation of the material in this publication do not imply the expression of any opinion whatsoever on the part of the World Health Organization concerning the legal status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. Dotted lines on maps represent approximate border lines for which there may not yet be full agreement. The mention of specific companies or of certain manufacturers' products does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This leads to the formation of an infectious granuloma that might have been responsible for the splenomegaly observed in about a third of the patients in this study. The findings also showed that lymphadenopathy and hepatomegaly were common, corroborating with previous research [6].…”
Section: Discussionsupporting
confidence: 91%
“…This leads to the formation of an infectious granuloma that might have been responsible for the splenomegaly observed in about a third of the patients in this study. The findings also showed that lymphadenopathy and hepatomegaly were common, corroborating with previous research [6].…”
Section: Discussionsupporting
confidence: 91%
“…Hematological complications such as anemia, leukopenia and thrombocytopenia are common in the course of brucellosis, and pancytopenia may be observed less frequently [3,5]. These hematological complications are more common in acute brucellosis cases (as opposed to relapse cases) and in patients with growth in blood culture [28]. These complications are typically mild and resolve promptly with antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The cases reported in Sweden were mostly due to the travelers arriving from the countries where brucellosis is endemic. In the USA, brucellosis is found commonly in immigrant families, especially in border states such as Texas (Serpa et al, 2018). However, B. abortus has not been reported in Western and Northern Europe, Canada, Japan, Israel, Australia and New Zealand (Adetunji et al, 2019).…”
Section: Epidemiologymentioning
confidence: 99%